Антология выдающихся достижений в науке и технике. Часть 16: Открытия и изобретения в металлургии - Баранов, Михаил Иванович (НТУ "ХПИ", 2013)
Приведён краткий очерк из всемирной истории изобретения человечеством основных металлургических технологий кустарного и промышленного производства различных металлов и сплавов.

A brief scientific essay on the history of invention of the main metallurgical technologies of artisan and industrial production of various metals and alloys is presented.
An anthology of outstanding achievements in science and technology. Part 16: Discoveries and inventions in metallurgy
Keywords: металл; сплав; промышленное производство; штейн; history; discovery; invention; metallurgy